Development of a reverse genetics system for West Nile virus (Kunjin type) - Wu, Zhen; Hu, Tao; Zhou, Zhou; He, Yu; Wang, Tao; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; et al. (Frontiers in Veterinary Science, 2025)
Kunjin virus (KUNV), a naturally attenuated strain of West Nile virus (WNV), shares similar transmission modes and hosts—primarily mosquitoes, birds, and horses. Globally, reverse genetics is the principal methodology for characterizing the molecular etiology of flaviviruses. In this study, cytomegalovirus (CMV) promoter-driven KUNV reporter replicons were engineered to incorporate three distinct reporter genes: Nanoluc, oxGFP, and mCherry. These replicons demonstrated successful translation and replication in mammalian (BHK-21), avian (DEF), and avian hepatic (LMH) cell lines. Additionally, an in vitro pseudovirus packaging system for KUNV was established using helper plasmids expressing either full-length C-prM/E or a truncated C-terminal variant (C18-prM/E). Both plasmids efficiently packaged replicon RNA into pseudoviruses, with C18-prM/E showing significantly higher packaging efficiency than full-length C-prM/E. Furthermore, leveraging a previously developed full-length infectious KUNV clone, a stable reporter virus was generated by inserting the NanoLuc luciferase gene. The reporter virus maintained genomic integrity over five serial passages with no loss of the reporter gene. Collectively, these experiments establish robust in vitro reverse genetics systems for KUNV. These tools constitute valuable molecular resources for investigating the KUNV lifecycle, advancing antiviral drug screening, and facilitating vaccine development.